A case of hemichorea‐hemiballism presenting in association with diabetic ketoacidosis. (March 2017) - Kurdi, Hibba; Ershaid, Dana; Evans, Peter
Abstract: Movement disorders are a rare but recognised manifestation of non‐ketotic hyperglycaemic episodes on a background of poorly‐controlled diabetes mellitus. The literature is otherwise sparse when it comes to an association between hemichorea‐hemiballism and diabetic ketoacidosis (DKA). A patient with no past medical history of note was admitted with a sudden‐onset involuntary movement disorder and was found to be in DKA during her inpatient stay. There was a delay in diagnosis and management as all efforts pointed in the direction of diagnosing the cause of the sudden‐onset hemichorea‐hemiballism as a potential cerebrovascular event. The movements subsided with treatment of the ketoacidosis and with the addition of tetrabenazine. Imaging revealed a hyperdensity of the left basal ganglia consistent with a metabolic cause and not an ischaemic event. Although the pathophysiology of movement disorders in diabetes is still unclear, this case highlights the importance in maintaining a wide list of differentials when faced with an atypical presentation of hemichorea‐hemiballism, especially as DKA is a reversible emergency with high mortality rates if left untreated. Hemichorea‐hemiballism as a consequence of DKA seems to be a multifactorial phenomenon. In this case, it began with non‐ketotic hyperglycaemia and evolved into ketoacidosis. Confounding factors precipitating this included infection, and delayed diagnosis and management. Copyright © 2017 John Wiley & Sons.